Optimization method for accurate positioning seeding based on sowing decision - Zhao, Xueguan; Chen, Liping; Gao, Yuanyuan; Yang, Shuo; Zhai, Changyuan (International Journal of Agricultural and Biological Engineering, 2021)
Variable seeding by sowing decision can improve the utilization rate of resources. In order to achieve more accurate position control and sowing rate control, precision sowing decision control system was developed, and the integral separation Proportional Integral Derivative (PID) control algorithm of metering disc speed and grid based dead reckoning method were proposed. In order to test the performance of the system, the experiment of the influence of integral switching on step response and the experiment of seeding response based on simulated sowing decision were carried out. The results showed that average lag distance based on dead reckoning was 72.2 cm less than that of non-dead reckoning; system response distance of integral separation PID control algorithm was 43.1 cm shorter than that of ordinary PID control algorithm. The field experiment showed that the error of the monitoring sowing rate relative to the actual sowing rate was 3.5%, the average transition distance within the speed range of 3-9 km/h was 139.5 cm, and the standard deviation was 12.8 cm. The developed seeding control system improves the accuracy of seeding based on sowing decision, and provides a technical reference for low-cost sowing decision based control system in China. Keywords: sowing decision, positioning sowing, precision seeding control, lagging model, electric drive seed-metering DOI: 10.25165/j.ijabe.20211403.5758 Citation: Zhao X G, Chen L P, Gao Y Y, Yang S, Zhai C Y. Optimization method for accurate positioning seeding based on sowing decision. Int J Agric & Biol Eng, 2021; 14(3): 171–180.